Social Values In The Barter Tradition In Wulandoni Market, Lembata District. - Simbolon, Gallex; Klau, Erni Raster; Mardani, Ambara S; Udak, Yulia Priscilia (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
The problem in this study is what are the social values in the barter tradition in the Wulandoni market, Lembata district, with the aim of exploring more deeply the social values in the barter tradition in the Wulandoni market, Lembata district. Qualitative research methods with a phenomenological approach were conducted in Wulandoni Village, Wulandoni District, Lembata Regency. The subjects in the study were barter actors, community leaders and village heads. Data collection techniques were observation, interviews and documentation studies. Data analysis techniques were data reduction, data presentation, and drawing conclusions. The triangulation used was data source triangulation and technique triangulation. The results of the study showed that the barter tradition contains values adopted by coastal and inland communities. These values include the value of compassion where barter actors maintain the barter market because it has been more than 10, and the barter tradition has become a habit and can help people in meeting their living needs. In the barter tradition, there is also often a bargaining process until an agreement is reached between the two parties which is contained in the value of helping each other. The Wulandoni barter market is still maintained because it has become a legacy from our ancestors, this is contained in the value of a sense of belonging. The rules in the barter market are that before the whistle is blown, the barter process still uses money, but after the whistle is blown, transactions in the form of money are not used but barter transactions between goods and goods, this is contained in the value of discipline. In the Wulandoni barter market, where the coastal community sits on the east and the interior on the west, this is contained in the value of discipline. The value of harmony in life, it was found that in the Wulandoni barter market, barter actors who bring goods to be exchanged have an equivalent value. The barter system is considered to be very helpful for the community's economy.